FREEDOM OF CONTRACT IN MORTGAGE LOAN AGREEMENT AT PT. BANK CIMB NIAGA, TBK. IN MEDAN - Tommy Leonard; Elvira Fitriyani Pakpahan; Kevin Alexander (International Journal of Latin Notary, 2022)
In a credit agreement, the position of the bank as a creditor and the customer as a debtor is never balanced. The position of the bank is stronger than that of potential customers. Whereas freedom of contract can only achieve justice if the parties have a balanced bargaining power. Unbalanced bargaining power occurs when a strong party can impose his will on a weak party, until the weak party only follows the terms of the contract proposed to him. Given that in the credit agreement there has been a contractual relationship and the clauses tend to favor the bank as the creditor, in a credit agreement, mostly for debtors its only a take it of leave it option, so that the opportunity to negotiate as an initial process of obtaining an agreement is small and even neglected. The research is used a empiric juridical legal research method. Data sources from the research were derived from secondary data consisting of legal materials and legal documents that became the basic foundation for answering problems in this study. The results of this study revealed that the completion of defaults in the mortgage loan agreement can be made before it is executable. Settlement of the default can be done by reschedulling, re-requirements and rearrangegement.